EVALUASI IMPLEMENTASI SERVICE DESK PADA DIREKTORAT INFORMASI KEPABEANAN DAN CUKAI MENGGUNAKAN ITIL V3 - Utomo, Nurul Budi; Syamsuddin, Muhammad Anshar (Politeknik Keuangan Negara STAN, 2020)
ABSTRACTThe Service Desk at the Directorate General of Customs and Excise (DGCE) is managed by the Echelon II Unit, namely the Directorate of Customs and Excise Information (DCEI). The implementation of the Service Desk function that has been carried out by DGCE currently has a problem that is, there is still the completion of an incident ticket that exceeds the time of the Service Level Agreement (SLA). This study conducted an assessment of the DJBC Service Desk with qualitative methods using ITIL Service Support Self-Assessment Service Desk in the form of a questionnaire, The implication of the research is whether it can be known whether the implementation of the service desk is in accordance with best practice and organizational policy or not. The limitation of this study is that there is no assessment of the incident, problem, change, and release management. The questionnaire will be submitted to the manager of the Service Desk at the DCEI, which is the Information Technology Services Management section, then observations are made to look for supporting evidence for the answers. The results of the analysis of this study are of 9 levels of assessment, 7 levels can be passed while the other 2 levels cannot be passed, for this reason, the authors provide recommendations that can be used to improve the DGCE Service Desk.Keywords: Service Desk; ITIL; DGCEABSTRAKService Desk pada Direktorat Jenderal Bea dan Cukai (DJBC) di kelola oleh Unit Eselon II yaitu, Direktorat Informasi Kepabeanan dan Cukai (DIKC). Implementasi fungsi Service Desk yang telah dilakukan oleh DJBC saat ini memiliki masalah yaitu, masih adanya penyelesaian tiket insiden yang melampaui waktu Service Level Agreement (SLA). Penelitian ini melakukan penilaian terhadap Service Desk DJBC dengan metode kualitatif dengan menggunakan ITIL Service Support Self-Assessment Service Desk yang berbentuk kuesioner, implikasi dari penelitian adalah dapat diketahui apakah implementasi service desk sudah sesuai dengan best practice dan kebijakan organisasi atau belum. Batasan dari penelitian ini adalah tidak dilakukannya penilaian pada incident, problem, change dan release management. Kuesioner akan diajukan kepada pengelola Service Desk di DIKC yaitu bagian Manajemen Layanan Teknologi Informasi, selanjutnya dilakukan observasi untuk mencari bukti pendukung jawaban. Hasil dari analisis penelitian ini adalah dari 9 level penilaian, 7 level dapat dilewati sedangkan 2 level yang lain belum dapat dilewati, untuk itu penulis memberikan rekomendasi yang dapat digunakan untuk perbaikan Service Desk DJBC.Kata Kunci: Service Desk, ITIL, DJBC